ASSESSMENT OF THE EFFECTIVENESS OF EDUCATIONAL PROGRAMS IN PATIENTS WITH METABOLIC SYNDROME - L. L. Kirichenko; K. V. Ovsyannikov; S. A. Tochilkina; A. P. Korolev; S. N. Strelkova (Столичная издательская компания, 2015)
Aim. To assess the effectiveness of educational programs in the treatment of patients with metabolic syndrome (MS).Material and methods. Patients with MS (n=68) were randomized into two groups of 34 people. Patients of the first group received standard antihypertensive therapy, while patients of the second group antihypertensive therapy and educational programs additionally. Examinations of carbohydrate, lipid and purine metabolism, blood pressure (BP) monitoring, anthropometric tests were performed before and after 24 weeks of therapy.Results. Stable target BP levels [24 (70%) patients in Group 1 and 29 (85%) patients in Group 2] and improvement in metabolic parameters were achieved in patients of both groups. Besides in patients of the second group received additional trainings improvement of anthropometric indicators (decrease in waist circumference from 106±6.5 to 94±2.4 cmand body weight from 99±3.5 to 79±6.3 kg) was found.Conclusion. The complex treatment of patients with MS should include educational programs in addition to antihypertensive drugs.